A major practicum at Kraft Foods (Philippines), Inc. Sucat, Parañaque City, Metro Manila - Cortel, Kristine Abris (2007)
The plant practice was conducted at Kraft Foods Inc., Philippines, Parañaque City, Metro Manila from April 11 to May 29, 2006. For 288 hours, the proponent exposed in the raw and packaging materials section. She was directly involved in the quality assessment of raw materials, packaging materials, and finished goods through organoleptic and physical testing, review of products standards and filing of documents such as receiving reports on raw and packaging materials. Moreover, she witnessed the application of principles in the operation of different equipment used in the company. She was able to gain knowledge about the company profile, products manufactured such as processed cheese blocks, processed cheese spreads and spoonables; and the good manufacturing practices (GMP) that the company follows. All throughout the activities, the proponent developed interpersonal relationship with the people in the Quality Systems Department. The student's manuscript is the written output of the information gathered from the 288-hour of plant practice. These include the company profile, technical analyses done in the laboratory, problems encountered and recommendations.